Analyzing Continuous Integration Bad Practices in Closed-Source Projects: An Initial Study - Silva, Ruben Blenicio Tavares; Bezerra, Carla I. M. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Continuous integration (CI) is a process widely used in projects of different types and sizes, generally aimed at improving development and also ensuring the quality of the software. However, some bad practices can mitigate or invalidate the beneficial effects of CI. In this context, we present an initial study to analyze CI bad practices in two closed-source projects. The study had as main research questions: (i) the frequency of CI bad practices in projects, (ii) the time that builds failures remain unresolved in projects, and (iii) the effects of CI bad practices on software health from the perspective of developers and project managers. For this, we carried out a mapping of the existence of bad practices through a questionnaire directed to the projects team. Also, it was realized the analysis of the pipeline history of the projects. Our findings indicate that the most common CI bad practices are related to improper management of the CI repository, and defective builds usually take a long time to fix. Besides, we found that the difficulties resulting from CI bad practices promote an increase in the development cost and reduction of software quality assurance.